THE EFFECT OF MINIMUM WAGE, EDUCATION LEVEL AND GROSS REGIONAL DOMESTIC PRODUCT ON LABOR RASOPTION INDONESIA 2010-2019 - Putri, Febriyanti Safdi; Mukhtar, Saparuddin; Wiralaga, Harya Kuncara (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
The purpose of this study was to determine the validity, truthfulness, authenticity and reliability of the extent to which the minimum wage, education level, and gross regional domestic product labor absorption in Indonesia. This study uses a quantitative descriptive method using panel data analysis techniques that combine times series data with cross section data. The type of data used in this study is secondary data, obtained from the Central Statistics Agency and other government agencies. The results obtained in this study are that the minimum wage has a positive and insignificant effect on employment in Indonesia, while the level of education and regional domestic products has a positive and significant effect on employment in Indonesia. Simultaneously, the minimum wage, education level and gross regional domestic product have an effect on employment.